PURCHASING DECISIONS: IN TERMS OF SERVICE QUALITY, PACKAGING, AND DISTRIBUTION CHANNELS OF FROZEN FOODS AT RUMAH HOKY NAGET - Ong, Virginia; Sri Rezeki; Associate Prof. Dr. Muhammad Hafiz Abd Rashid (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
Rumah Naget Hoky is a frozen foods product retail unit in Medan City that has established since 2018. As a part of the frozen foods supply chain, Rumah Naget Hoky has taken a role in connecting producers with end consumers by utilizing available distribution channels, using the best packaging, and trying to provide the best quality service to consumers. The purchasing decision frozen foods from Rumah Naget Hoky is one of the factors that determine its sustainability. This study aims to review the purchasing decision of frozen foods Rumah Naget Hoky in terms of service quality, packaging, and distribution channels. This study uses a quantitative method with the population in this study being all consumers of Rumah Naget Hoky. The research sample was obtained using the Hair et al. formula so that 200 respondents were obtained. The research instrument used a questionnaire with a Likert measurement scale. The results showed that service quality, packaging, and distribution channels have a positive and significant effect on purchasing decisions for frozen foods at Rumah Naget Hoky.